Consequences of the CJEU Ruling of 3 October 2019 on Swiss Franc Mortgage Loans for Polish Borrowers - Wilk, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2020)
The article discusses the effects of the recent ruling of the Court of Justice of the European Union (the CJEU), regarding the impact of abusive contractual provisions included in the foreign currency loan contracts on the legal effectiveness of the entire contract. The position of the CJEU may trigger the necessity to modify and unify the previous sentencing guidelines. Moreover, it may become necessary to revoke some final judgements in cases of individual borrowers that have been issued so far. The author analyses the direction the case law will take after the CJEU’s ruling and its impact on cases which have already been closed.